(untitled) (Khairulummah, 2023)
In the Persian literary work the Seerah (Biography of the Prophet PBUH) and praises of the Prophet (peace and blessings of Allah be upon him) are found in abundance and the most significant contribution is the poem "Maghazi-ul-Nabi" written by Sheikh Yaqoob Al-Sarafi. This work is a unique and comprehensive sample of Prophetic history which is still anonymous. In this paper, an attempt has been made to find out the components of "Maghazi-ul-Nabi" by "Sheikh Yaqoob Al-Sarafi" and the method of narration of the biography of the Prophet, peace be upon him. The analysis of the structure of Mughazi-ul-Nabi (peace be upon him) in writing with detailed analytical approach and depiction of beliefs are discussed. The result of the research shows that writers and historiographers have described the details of the Prophet’s life in a systematic way. Sheikh Yaqoob Al-Sarai used ancient poetic and eloquent language to achieve this goal.He had tried to describe the history of the Prophet (PBUH) in simple words and easy poetic style in which the narrative quality dominates the poetic elements of the text.